Analisis Pengaruh Pertumbuhan Ekonomi, Rasio Gini, Pengangguran, Indeks Pembangunan Manusia, Kepadatan Penduduk, Dan Kemandirian Keuangan Daerah Terhadap Kemiskinan Di Provinsi Jawa Barat Tahun 2017-2022 - Dyah Mustikaningrum; Yuni Prihadi Utomo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Poverty is a common global issue, especially in developing countries like Indonesia. This study aims to evaluate the impact of Economic Growth, Gini Ratio, Unemployment Rate, Human Development Index (HDI), Population Density, and Regional Fiscal Independence Level on poverty levels in West Java Province. The method used is panel data regression analysis, which combines time series data from 2017 to 2022 and cross-section data from 28 districts/cities in the province. Based on the results of the analysis, the best model chosen is the Fixed Effect Model (FEM). The research findings show that the Gini Ratio, Unemployment, and Regional Financial Independence have a significant effect on poverty. Income inequality and high unemployment rates are known to worsen poverty conditions, while the ability of regions to manage their own finances actually contributes to reducing poverty rates. On the other hand, variables such as Economic Growth, HDI, and Population Density do not have a significant effect on poverty during the observation period. These findings underline the importance of efforts to equalize income, create jobs, and increase fiscal independence in reducing poverty rates in West Java.